Comparative legal analysis of the uniate and the federal union of Slavic states in the XII–XVI centuries - Seregin, Andrei V. (Journal of the Belarusian State University. Law, 2019)
Examines the doctrine of the unitarian and federal form of government and territorial structure during the classical and late Middle Ages, as a specific phenomenon of large Slavic nations. Examples of real and personal uny Hungarian-Croatian Kingdom and the Commonwealth, and especially the patrimony of the Federal relations within the Croatian state and the Grand Duchy of Lithuania, Russian and Zhmudskaya. Regularities of the integration of political and legal processes in medieval Slavic world. The conclusion is made about the unitary state-territorial relations in the Polish Kingdom, one of the subjects of the Unitarian union of the Lithuanian-Russian state. We should call a Medieval Federation – the Patrimonial Federations. Noted, the ability to self-organization and political unification of the Slavic peoples in a complex public education. It is proved that the unification of the Slavic states in the XII–XVI centuries took place not only within the framework of a highly centralized state mechanism, but also on the basis of local characteristics with the recognition of the widest autonomy of different communities, cities, principalities and kingdoms, uniting in a single union state. Substantiates the possibility of using Slavic historical and legal experience in the creation of a new union of Slavic states, in the future, and in the near present.
Keywords: Slavs; union; the Patrimonial Federation; the Kingdom of Croatia; the Kingdom of Poland; the Grand Duchy of Lithuania; the state-territorial structure; the Middle Ages